2019
DOI: 10.3389/fphys.2019.00217
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Novel Nutraceutical Compound Containing Red Yeast Rice, Polymethoxyflavones and Antioxidants in the Modulation of Cholesterol Levels in Subjects With Hypercholesterolemia and Low-Moderate Cardiovascular Risk: The NIRVANA Study

Abstract: Background: Red yeast rice supplements are broadly accepted as treatment for dyslipidaemia in subjects without high cardiovascular (CV) risk. Their effect on lipid profile is well known, but few data are available on their effect on endothelial function.Objectives: To study the effect of a novel nutraceutical compound (NC) containing low monacolin K dose, polymethoxyflavones and antioxidants on lipid profile, endothelial function and oxidative stress.Methods: Fifty-two subjects with low-moderate CV risk and dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…This compound has not been reported for any variety of hemp so far. Furthermore, it belongs to the class of polymethoxyflavones that have anti-inflammatory and anti-carcinogenic activities and occur as "novel nutraceutical compounds" [36]. In order to perform its absolute identification, it is necessary to isolate it from the inflorescence and define it with a more detailed analytical approach, also including NMR analysis.…”
Section: Quantification Of Cannabinoids By Hplc-q-exactive-orbitrap ®mentioning
confidence: 99%
“…This compound has not been reported for any variety of hemp so far. Furthermore, it belongs to the class of polymethoxyflavones that have anti-inflammatory and anti-carcinogenic activities and occur as "novel nutraceutical compounds" [36]. In order to perform its absolute identification, it is necessary to isolate it from the inflorescence and define it with a more detailed analytical approach, also including NMR analysis.…”
Section: Quantification Of Cannabinoids By Hplc-q-exactive-orbitrap ®mentioning
confidence: 99%
“…With mean reductions of 13.9% and 19.7%, respectively, the cholesterol-lowering efficacy of the nutraceutical tested in the current trial compares favorably with the results of this meta-analysis, probably because of a higher dose of monacolin K in Aquilea Colesterol ® compared with that nutraceutical. A 15.6% LDL-c reduction was observed in a recent clinical trial of a novel nutraceutical also containing 3 mg monacolin K plus various antioxidants [40]. In this trial hs-CRP was not lowered, but LDL oxidation was reduced and endothelial function improved, pointing to an added cardiovascular benefit of such nutraceutical combinations.…”
Section: Discussionmentioning
confidence: 71%
“…We have shown that the levels of apoptosis in HUVECs treated with serum from stable and acute CAD patients reflect the gravity of the disease [53,54]. Furthermore, we have reported that this assay can reliably detect a reduction in apoptosis in HUVECs treated with serum from stable CAD/COPD patients following treatment with ticagrelor [6] or from subjects with hypercholesterolemia and low-moderate cardiovascular risk, following eight weeks consumption of a red yeast rice, polymethoxyflavones, and antioxidants containing nutraceutical supplement [55]. In another study by our group, this approach was used, in parallel with measurements of changes in brachial wall shear stress and flow mediated dilation, to assess ED in patients that underwent surgical or transcatheter aortic valve replacement [56].…”
Section: Correlation Analyses Between Sirt1 and Hes1 Mrna Levels And mentioning
confidence: 93%